Mechanical stress-induced autophagic response: A cancer-enabling characteristic?. (November 2020) - Das, Joyjyoti; Chakraborty, Suman; Maiti, Tapas K.
Abstract: Metastasis is the leading cause of cancer mortality. Throughout the cascade of metastasis, cancer cells are exposed to both chemical and mechanical cues which influence their migratory behavior and survival. Mechanical forces in the milieu of cancer may arise due to excessive growth of cells in a confinement as in case of solid tumors, interstitial flows within tumors and due to blood flow in the vasculature as in case of circulating tumor cells. The focus of this review is to highlight the mechanical forces prevalent in the cancer microenvironment and discuss the impact of mechanical stresses on cancer progression, with special focus on mechanically induced autophagic response in cancer cells. Autophagy is a cellular homeostatic mechanism that a cell employs not only for recycling of damaged organelles and turnover of proteins involved in cellular migration but also as an adaptive response to survive through unfavourable stresses. Elucidation of the role of mechanically triggered autophagic response may lead to a better understanding of the mechanobiological aspects of metastatic cancer and unravelling the associated signaling mechanochemical pathways may hint at potential therapeutic targets.